2022
DOI: 10.1128/mbio.03458-21
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of the Human Pathogen Pseudomonas aeruginosa to the Neurotransmitter Acetylcholine

Abstract: P. aeruginosa causes a significant number of deaths annually worldwide. For many pathogens, chemotaxis plays an import role in the initial stages of infection, and deciphering the key chomoeffectors and their cognate chemoreceptors may permit the development of strategies to inhibit this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 107 publications
1
42
0
Order By: Relevance
“…There is an almost unlimited number of different ligands that bind to extracytosolic LBDs, which can thus be used for the development of novel biosensors. These compounds include clinically important compounds such as the neurotransmitters epinephrine ( 77 ), γ-aminobutyric acid (GABA) ( 56 ), histamine ( 78 ) or acetylcholine ( 79 ), antimicrobial peptides ( 80 ), amino acids ( 40 ), organic acids ( 46 ), sugars ( 81 ), fatty acids ( 82 ), quorum-sensing molecules ( 39 ), plant hormones ( 83 ), aromatic hydrocarbons ( 84 ), purines ( 41 ), polyamines ( 25 ), quaternary amines ( 85 ), nitrate ( 86 ), inorganic phosphate ( 87 ), and specific metal cations ( 88 ) or oxanions ( 30 ). The demonstration that extracytosolic LBDs maintain their capacity to sense their ligands over a wide pH range will permit the construction of biosensors that are robust and able to withstand changes in the analyte medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an almost unlimited number of different ligands that bind to extracytosolic LBDs, which can thus be used for the development of novel biosensors. These compounds include clinically important compounds such as the neurotransmitters epinephrine ( 77 ), γ-aminobutyric acid (GABA) ( 56 ), histamine ( 78 ) or acetylcholine ( 79 ), antimicrobial peptides ( 80 ), amino acids ( 40 ), organic acids ( 46 ), sugars ( 81 ), fatty acids ( 82 ), quorum-sensing molecules ( 39 ), plant hormones ( 83 ), aromatic hydrocarbons ( 84 ), purines ( 41 ), polyamines ( 25 ), quaternary amines ( 85 ), nitrate ( 86 ), inorganic phosphate ( 87 ), and specific metal cations ( 88 ) or oxanions ( 30 ). The demonstration that extracytosolic LBDs maintain their capacity to sense their ligands over a wide pH range will permit the construction of biosensors that are robust and able to withstand changes in the analyte medium.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotaxis assays were performed as previously described ( 79 ) with some modifications. When cultures reached an OD 660 of 0.4, the cells were gently washed twice with chemotaxis buffer at different pH and then resuspended in fresh buffer.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we selected chemoreceptors that showed significant variation in different growth media and for which it was shown that the mutation of the corresponding gene abolished chemotaxis to a given chemoattractant. These receptors were PctC, PctD, and McpK, for which we have shown previously that a deletion or inactivation of the corresponding gene has suppressed chemotaxis to GABA [ 72 ], choline [ 20 ], or α-ketoglutarate [ 77 ], respectively. This implies that responses of the wild type strain to these compounds are entirely due to the action of these receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas in a canonical two-component system one sensor protein controls the phosphorylation state of its cognate response regulator, in chemosensory pathways typically many chemoreceptors control the phosphorylation state of CheY. Chemoreceptor abundance is thus proposed to define the weight by which a given receptor contributes to defining the final response, as supported by different studies in which specific chemoreceptors were overexpressed [ 20 , 21 , 22 , 23 ]. Here we have used proteomics to analyze chemoreceptor protein amounts in P. aeruginosa —a model bacterium in the field of signal transduction [ 9 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation